Risk analysis in manufacturing footprint decisions - Rösiö, Carin; Bruch, Jessica; Wiktorsson, Magnus; Bellgran, Monica (Cranfield University Press, 2013)
A key aspect in the manufacturing footprint analysis is the risk and sensitivity analysis of critical parameters. In order to contribute to efficient industrial methods and tools for making well-founded strategic decisions regarding manufacturing footprint this paper aims to describe the main risks that need to be considered while locating manufacturing activities, and what risk mitigation techniques and strategies that are proper in order to deal with these risks. It is also proposed how the risk analysis should be included in the manufacturing location decision process.
Keywords: risk analysis; manufacturing location decision process; manufacturing footprint